Prospective Science Student Teachers’ Online Learning Environment Experiences: Measurement Based on the Net Promoter Score - Mahdiannur, Muhamad Arif; Martini; Astriani, Dyah; Rosdiana, Laily; Fauziah, An Nuril Maulida (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Personalization is used in online learning to help students achieve SDG 4.C and Education 4.0 indicators. Not many studies have revealed prospective science student teachers’ online learning experiences. A good experience will provide positive and constructive self-knowledge for prospective science student teachers in designing 21st-century digital learning. This study aimed to inquire into prospective science student teachers’ views on online learning using the Net Promoter Score survey. This study involved 29 prospective science student teachers at one of the public universities in Indonesia. This study revealed that online learning provides freedom to express opinions and ideas freely, helps evaluate learning outcomes, online educational resources help understand the contents, and online simulations help understand concepts. The negative experiences in the online learning environment include the lack of interaction with lecturers, online learning has not yet built creative, innovative, and critical thinking skills and has not supported competency development. There is a significant difference between positive and negative online learning experiences, demonstrating how experiences can impact future teacher conception. Based on our findings, recommendations were provided to assist university lecturers in creating and designing an online learning environment to develop the professional competencies of prospective science student teachers.